Agreement between lower esophageal and nasopharyngeal temperatures in children ventilated with an endotracheal tube with leak. Issue 2 (16th December 2015) - Snoek, Aarjan P.; Saffer, Emily
Summary: Background: A temperature probe placed in the lower third of the esophagus accurately reflects core temperature in anesthetized children. Temperature probes are commonly placed in the nasopharynx in children, but when utilizing an uncuffed endotracheal tube (ETT) with a softly audible leak, ventilated gases from the trachea can escape upwards toward the nasopharynx, thereby potentially causing a cooling effect in the nasopharynx. Objectives: We sought to establish if nasopharyngeal and lower esophageal temperatures are in agreement in children undergoing general anesthesia, both in scenarios of ventilation with a cuffed ETT that has minimal or no leak (cuff up), as well as an ETT with leak (cuff down). Methods: A prospective, crossover agreement study was performed on anesthetized children. Children were intubated with a MicroCuff ® ETT and had temperature probes inserted into both the nasopharynx and lower esophagus. Under standardized ventilator and gas flow settings, temperatures were recorded with the ETT cuff inflated, and with the cuff deflated. Bland–Altman plots were utilized to assess agreement of temperatures. Results: Fifty patients successfully completed this study. The mean difference between esophageal and nasopharyngeal temperature was found to be −0.03°C in the presence of minimal or no leak around the ETT (cuff up), with 95% limits of agreement (LOA) of −0.22 to 0.15°C. The mean difference between esophageal and nasopharyngeal temperature was found to be 0.1°C when a larger leak existed around the ETT (cuff down), with LOA of −0.31 to 0.51°C. Conclusions: Nasopharyngeal temperature accurately reflects lower esophageal temperature when there is minimal or no ETT leak. When a larger ETT leak is present, nasopharyngeal temperature is on average 0.1°C cooler than lower esophageal temperature. As the nasopharyngeal temperature probe site confers the advantage of simplicity of accurate placement compared to its esophageal counterpart, our findings support the use of nasopharyngeal temperature probes in children ventilated with both cuffed and uncuffed ETTs. Abstract :